2015
DOI: 10.1016/j.jmb.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Function of Group II Chaperonins

Abstract: Protein folding in the cell requires the assistance of enzymes collectively called chaperones. Among these, the chaperonins are 1 MDa ring-shaped oligomeric complexes that bind unfolded polypeptides and promote their folding within an isolated chamber in an ATP-dependent manner. Group II chaperonins, found in archaea and eukaryotes, contain a built-in lid that opens and closes over the central chamber. In eukaryotes, the chaperonin TRiC/CCT is hetero-oligomeric, consisting of two stacked rings of eight paralog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
169
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 110 publications
(143 reference statements)
2
169
2
Order By: Relevance
“…In their action in protein folding, chaperonins bind protein substrates in the absence of ATP, whereas their release is accompanied by the hydrolysis of ATP (17)(18)(19). We found that in this case, too, the dissociation of the chaperonin from mitotic checkpoint complexes requires ATP, as assayed by the release of CCT5 from immunoprecipitated complexes to supernatants (Fig.…”
Section: Significancementioning
confidence: 67%
See 4 more Smart Citations
“…In their action in protein folding, chaperonins bind protein substrates in the absence of ATP, whereas their release is accompanied by the hydrolysis of ATP (17)(18)(19). We found that in this case, too, the dissociation of the chaperonin from mitotic checkpoint complexes requires ATP, as assayed by the release of CCT5 from immunoprecipitated complexes to supernatants (Fig.…”
Section: Significancementioning
confidence: 67%
“…A great body of previous work described actions of CCT/TRiC chaperonin in the folding of proteins to their native states (reviewed in refs. [17][18][19]. It is a complex composed of two rings of eight homologous subunits surrounding a central cavity, where folding is thought to take place.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations